Mathematical Learning Experiment Using Numbered Heads Together And Think Pair Share Models, Examined From The Learning Style - Muhaimin, Lukman Hakim; Mukhibin, Ahmad; Mitrayana, Mitrayana; Dasari, Dadan (Journal of Mathematics and Mathematics Education, 2022)
This study aims to determine the effect of the NHT and TPS learning models on mathematics learning outcomes, the impact of student learning styles on mathematics learning outcomes, and the result of the interaction of learning models and student learning styles on mathematics learning outcomes. This type of quantitative research with a quasi-experimental design. The research sample consisted of two classes (experimental and control) which were taken using Cluster Random Sampling from the population of all course VIII students of SMP 4 Muhammadiyah Surakarta in the academic year 2021/2022. Data collection techniques with questionnaires and tests. Before the research, a balance test was conducted to determine whether the two samples had the same initial abilities. The normality test and homogeneity test are prerequisite analysis tests in this study. The data analysis technique using two-way cell analysis of variance is different, with a significance level of 5%. The results showed that the NHT and TPS learning models affected mathematics learning outcomes. The mathematics learning outcomes of students who were given the NHT learning model tended to be better than those who were given the TPS learning model. Learning styles affect the results of learning mathematics. Students with an auditory learning style get better learning results than visual and kinesthetic learning styles. The interaction between the NHT and TPS learning models on mathematics learning outcomes in terms of student learning styles